STUDY OF ENZYME-CATALYSED AND NONCATALYSED INTERACTIONS BETWEEN SOIL HUMIC ACID AND 13C-LABELLED 2-AMINOBENZOTHIAZOLE USING SOLID-STATE 13C NMR SPECTROSCOPY - Witte E.G.; Philipp H.; Vereecken H. (My University, 2002)
Chemical interactions between 2-aminobenzothiazole (ABT) and a soil humic acid (HA) extracted from a gleyic planosol were investigated by solid-state 13C CP/MAS NMR spectroscopy. Reactions of the HA with ABT 13C-labelled at the C-2 position were performed in aqueous solution under noncatalysed and enzyme-catalysed conditions. Without enzymic catalysis the amount of ABT-2-13C taken up by soil HA in an oxygen atmosphere was about twice the uptake under argon. In the presence of the oxidative enzyme laccase and air, about three times as much ABT was bound to HA as compared to the uptake in a control experiment with inactivated laccase. The results suggest that oxidation reactions of the humic acid significantly enhance the extent of binding between ABT and HA. The 13C NMR spectra of the HA-ABT adducts indicated that in both noncatalysed and enzyme-catalysed reactions ABT may be bound to humic acid by noncovalent as well as covalent bonds.